BODY STALK ANOMALY TIPE IV DENGAN OMFALOKEL BESAR PADA KEHAMILAN TRIMESTER TIGA: LAPORAN KASUS - Saragih, Reynhard; Sari, Ratna Dewi Puspita (CV. Jasa Sukses Abadi, 2025)
Body stalk anomaly (BSA) is a rare and severe congenital malformation with an estimated incidence of approximately 1 in 14,000 births, and the majority of cases result in intrauterine death. Early detection of BSA is essential to differentiate it from exomphalos, which carries a significantly better prognosis. The exact etiology of BSA remains unclear, although chromosomal analyses have been conducted to investigate potential genetic abnormalities in affected fetuses. We report a case of a 35-year-old pregnant woman who presented to Dr. H. Abdul Moeloek General Hospital with complaints of premature rupture of membranes two hours prior to admission. A fetomaternal ultrasound examination revealed an intrauterine fetal demise in transverse lie, with a large omphalocele containing the small intestine, large intestine, liver, right kidney, and urinary bladder located outside the abdominal cavity. Additional findings included vertebral scoliosis and a short umbilical cord, with no other apparent major congenital anomalies. Biometric measurements were: BPD 80.7 mm, FL 54.4 mm, and HL 50.5 mm. The ultrasound impression concluded a diagnosis of body stalk anomaly. Early prenatal diagnosis using ultrasonography is feasible from 11 weeks of gestation, enabling detailed evaluation of fetal anatomy and abnormalities. Unlike gastroschisis and omphalocele, which are frequently associated with chromosomal abnormalities such as trisomy 18, 13, and 21, as well as Turner, Klinefelter, and triploidy syndromes, chromosomal aberrations in BSA are rarely reported, though mosaicism of 45,X and chromosome 16 polymorphisms have been documented.